2007
DOI: 10.1016/j.expneurol.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal infusion of a Ca2+-permeable AMPA channel blocker slows loss of both motor neurons and of the astrocyte glutamate transporter, GLT-1 in a mutant SOD1 rat model of ALS

Abstract: Elevated extracellular glutamate, resulting from a loss of astrocytic glutamate transport capacity, may contribute to excitotoxic motor neuron (MN) damage in ALS. Accounting for their high excitotoxic vulnerability, MNs possess large numbers of unusual Ca 2+ permeable AMPA channels (Ca-AMPA channels), the activation of which triggers mitochondrial Ca 2+ overload and strong reactive oxygen species (ROS) generation. However, the causes of the astrocytic glutamate transport loss remain unexplained. To assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…This could, in theory, lead to a greater proportion of Ca 2ϩ -permeable AMPA receptors, which could increase glutamate-induced motor neuron excitotoxicity caused by increased [Ca 2ϩ ] i . In addition, Yin et al (2007) demonstrated that intrathecal infusion of NAS reduced motor neuron loss in G93A rats. This effect presumably is caused by action on Ca 2ϩ -permeable AMPA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This could, in theory, lead to a greater proportion of Ca 2ϩ -permeable AMPA receptors, which could increase glutamate-induced motor neuron excitotoxicity caused by increased [Ca 2ϩ ] i . In addition, Yin et al (2007) demonstrated that intrathecal infusion of NAS reduced motor neuron loss in G93A rats. This effect presumably is caused by action on Ca 2ϩ -permeable AMPA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The answer may be found in the functionality of these specialized neurons: if the AMPA glutamate receptors are blocked, the viability of the cells increases and the amount of mutant SOD1 inclusions formed is reduced (Yin et al, 2007;Tortarolo et al, 2006;Tateno et al, 2004;Rembach et al, 2004).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 98%
“…However, a marked loss of ventral-horn EAAT2 was observed, along with substantial motor-neuron damage, before onset of symptoms (90-100 days) in the SOD1-G93A rats. Compared with sham-treated SOD1-G93A animals, 30-day NAS infusions (starting at approximately 70 days of age) markedly diminished the loss of both motor neurons and of astrocytic EAAT2 labeling (157). Interestingly, a recent study showed that, under normal conditions, astrocytes regulate the expression and subunit composition of the AMPA receptors in motor neurons.…”
Section: Glutamate Receptor-mediated Excitotoxicity In Alsmentioning
confidence: 99%
“…In support of a crucial role for GluR2 in controlling Ca 2þ influx through the AMPA-receptor complex, the evidence indicates that the overexpression of a GluR2-deficient Ca 2þ -permeable AMPA receptor in mice leads to a late-onset motorneuron degenerative disorder, which is exacerbated when coexpressed with the mutant SOD1 transgene (78,79). To assess the role of Ca 2þ -permeable AMPA receptors on the evolution of ALS pathology in vivo, Yin and colleagues (157) examined the effects of prolonged intrathecal infusion of the AMPA channel blocker, 1-naphthyl acetylspermine (NAS), in SOD1-G93A transgenic rat. In wild-type animals, immunoreactivity for EAAT2 was particularly strong around ventral horn motor neurons.…”
Section: Glutamate Receptor-mediated Excitotoxicity In Alsmentioning
confidence: 99%